Involvement and prognosis value of CD8+ T cells in giant cell arteritis. (August 2016) - Samson, Maxime; Ly, Kim Heang; Tournier, Benjamin; Janikashvili, Nona; Trad, Malika; Ciudad, Marion; Gautheron, Alexandrine; Devilliers, Hervé; Quipourt, Valérie; Maurier, François; Meaux-Ruault, Nadine; Magy-Bertrand, Nadine; et al.
Abstract: CD8 + T cells participate in the pathogenesis of some vasculitides. However, little is known about their role in Giant Cell Arteritis (GCA). This study was conducted to investigate CD8 + T cell involvement in the pathogenesis of GCA. Analyses were performed at diagnosis and after 3 months of glucocorticoid treatment in 34 GCA patients and 26 age-matched healthy volunteers. Percentages of CD8 + T-cell subsets, spectratype analysis of the TCR Vβ families of CD8 + T cells, levels of cytokines and chemokines and immunohistochemistry of temporal artery biopsies (TAB) were assessed. Among total CD8 + T cells, percentages of circulating cytotoxic CD8 T lymphocytes (CTL, CD3 + CD8 + perforin + granzymeB + ), Tc17 (CD3 + CD8 + IL-17 + ), CD63 + CD8 + T cells and levels of soluble granzymes A and B were higher in patients than in controls, whereas the percentage of Tc1 cells (CD3 + CD8 + IFN-γ + ) was similar. Moreover, CD8 + T cells displayed a restricted TCR repertoire in GCA patients. Percentages of circulating CTL, Tc17 and soluble levels of granzymes A and B decreased after treatment. CXCR3 expression on CD8 + T cells and its serum ligands (CXCL9, -10, -11) were higher in patients. Analyses of TAB revealed high expression of CXCL9 and -10 associated with infiltration by CXCR3 + CD8 + T cells expressing granzyme B and TiA1. The intensity of the CD8 T-cell infiltrate in TAB was predictive of the severity of the disease. This study demonstrates the implication and the prognostic value of CD8 + T-cells in GCA and suggests that CD8 + T-cells are recruited within the vascular wall through an interaction between CXCR3 and its ligands. Highlights: CD8 immune response is increased in giant cell arteritis (GCA). CXCR3 and its ligands are involved in the recruitment of CD8 + T cells. GCA is more severe when >6% of all cells are CD8 + T cells in temporal arteries.